No paleoclimatic anomalies are associated with the late Eocene extraterrestrial impact events - Bridget S. Wade; Natalie K. Y. Cheng (Communications Earth & Environment)
Abstract Two distinct extraterrestrial impacts events struck the Earth less than 25,000 years apart in the late Eocene, approximately 35.65 million years ago. These resulted in the Popigai (northern Siberia) and Chesapeake Bay (eastern North America) impacts structures, the largest of the Cenozoic era. To examine the paleoclimatic consequences attributed to the late Eocene Chesapeake and Popigai extraterrestrial impact events, we present multispecies planktonic and benthic foraminiferal oxygen (δ18O) and carbon (δ13C) isotope records. Here we generate data from the Gulf of Mexico, Deep Sea Drilling Project Site 94 covering 35.85 to 35.49 million years ago. No isotopic anomalies or excursions were recorded across the impact horizons. However, ~100,000 years before the impacts, a negative 0.75‰ δ18O shift occurs in planktonic foraminifera, coincident with a 0.25‰ positive change in benthic foraminifera. We interpret this as a warming of ~2 °C in the surface ocean, accompanied by 1 °C deep water cooling, but these modifications are before and not coeval with the impact horizons. Despite the close succession of two or more large extraterrestrial impact events within a short space of time (less than 25,000 years), our study from the Gulf of Mexico indicates no detectable paleoclimatic response.